Clinical utility of immature reticulocyte fraction for identifying early red blood cell regeneration in anemic dogs. (10th February 2023) - Jung, Jae‐Ha; Yang, Yeseul; Seo, Dansong; Cho, Soyeon; Choi, Goeun; Kim, Yongbaek
Abstract: Background: Evaluating regeneration is essential for the classification and differential diagnosis of anemia in dogs. Early detection of regeneration is challenging in anemic dogs. Objectives: This study assessed the value of immature reticulocyte fraction (IRF) in differentiating preregenerative anemia (PRA) from nonregenerative anemia (NRA) in dogs. Animals: Ninety‐four dogs: 49 controls and 45 with anemia. Methods: Case‐control study. Fractions of low‐, medium‐ (MFR), and high‐fluorescence reticulocytes (HFR), were measured using the ADVIA 2120i hematology analyzer. The IRF was calculated as the sum of percentages of MFR and HFR. Data from dogs with regenerative anemia (RA, n = 19), PRA (n = 11), and NRA (n = 15) were retrospectively analyzed. The value of IRF was compared with reticulocyte production index (RPI) using the receiver operating characteristic (ROC) curve. Results: The median of IRF was significantly higher in dogs with RA (46.5%; range, 40.9‐53.6%; P < .001) and PRA (40.6%; range, 27.7‐47.1%; P = .01) than in controls (22.1%; range, 16.9‐29.3%). The IRF in dogs with PRA showed no difference compared to dogs with RA ( P > .99) but was higher than dogs with NRA (18.7%; range, 8.8‐24%; P = .00). The area under the ROC curve of IRF was superior to that of RPI (0.897 vs 0.818, P = .00) in differentiating dogs with PRA from NRA. Conclusions and Clinical Importance: The IRF is a reliable variable for detecting early regeneration in anemic dogs without reticulocytosis. The study suggests that the measurement of IRF could be useful in classifying anemic dogs.